Development of flow cytometry‐based assays to assess the ability of antibodies to bind to SARS‐CoV‐2‐infected and spike‐transfected cells and mediate NK cell degranulation. Issue 6 (1st April 2022) - Mielke, Dieter; Stanfield‐Oakley, Sherry; Jha, Shalini; Keyes, Taylor; Zalaquett, Adam; Dunn, Brooke; Rodgers, Nicole; Oguin, Thomas; Sempowski, Greg D.; Binder, Raquel A.; Gray, Gregory C.; Karuna, Shelly; et al.
Abstract: Since the beginning of the SARS‐CoV‐2 pandemic, antibody responses and antibody effector functions targeting SARS‐CoV‐2‐infected cells have been understudied. Consequently, the role of these types of antibodies in SARS‐CoV‐2 disease (COVID‐19) and immunity is still undetermined. To provide tools to study these responses, we used plasma from SARS‐CoV‐2‐infected individuals ( n  = 50) and SARS‐CoV‐2 naive healthy controls ( n  = 20) to develop four specific and reproducible flow cytometry‐based assays: (i) two assessing antibody binding to, and antibody‐mediated NK cell degranulation against, SARS‐CoV‐2‐infected cells and (ii) two assessing antibody binding to, and antibody‐mediated NK cell degranulation against, SARS‐CoV‐2 Spike‐transfected cells. All four assays demonstrated the ability to detect the presence of these functional antibody responses in a specific and reproducible manner. Interestingly, we found weak to moderate correlations between the four assays (Spearman rho ranged from 0.50 to 0.74), suggesting limited overlap in the responses captured by the individual assays. Lastly, while we initially developed each assay with multiple dilutions in an effort to capture the full relationship between antibody titers and assay outcome, we explored the relationship between fewer antibody dilutions and the full dilution series for each assay to reduce assay costs and improve assay efficiency. We found high correlations between the full dilution series and fewer or single dilutions of plasma. Use of single or fewer sample dilutions to accurately determine the response rates and magnitudes of the responses allows for high‐throughput use of these assays platforms to facilitate assessment of antibody responses elicited by SARS‐CoV‐2 infection and vaccination in large clinical studies.